2011
DOI: 10.1073/pnas.1111255108
|View full text |Cite
|
Sign up to set email alerts
|

Lower specific infectivity of protease-resistant prion protein generated in cell-free reactions

Abstract: Prions are unconventional infectious agents that cause transmissible spongiform encephalopathy (TSE) diseases, or prion diseases. The biochemical nature of the prion infectious agent remains unclear. Previously, using a protein misfolding cyclic amplification (PMCA) reaction, infectivity and disease-associated protease-resistant prion protein (PrPres) were both generated under cell-free conditions, which supported a nonviral hypothesis for the agent. However, these studies lacked comparative quantitation of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 48 publications
6
45
0
Order By: Relevance
“…A recent study showed evidence of high infectivity titers in PMCA reactions with the hyper strain of transmissible mink encephalopathy, although incubation times per infectious unit were longer than those observed for brain-derived infectivity (51). A related report of a study performing careful quantitative comparisons of the PMCAgenerated infectivity titer versus the amount of PrP res has drawn attention to the fact that a significant fraction of PrP res generated in PMCA reactions may not be infectious (32). Consistent with this observation, albeit in the context of mutant PrP C molecules, PMCA seeding activity can be present in samples with limited infectivity (39).…”
Section: Mammalian Prions Are Thought To Consist Of Misfolded Aggregamentioning
confidence: 99%
“…A recent study showed evidence of high infectivity titers in PMCA reactions with the hyper strain of transmissible mink encephalopathy, although incubation times per infectious unit were longer than those observed for brain-derived infectivity (51). A related report of a study performing careful quantitative comparisons of the PMCAgenerated infectivity titer versus the amount of PrP res has drawn attention to the fact that a significant fraction of PrP res generated in PMCA reactions may not be infectious (32). Consistent with this observation, albeit in the context of mutant PrP C molecules, PMCA seeding activity can be present in samples with limited infectivity (39).…”
Section: Mammalian Prions Are Thought To Consist Of Misfolded Aggregamentioning
confidence: 99%
“…On the one hand, PMCA-derived PrP Sc products were shown to produce the same strain-specific disease phenotype in animals as brain-derived PrP Sc (16,18,24). On the other hand, differences in incubation times to disease by brain-and PMCAderived PrP Sc suggest the possibility of change in structure and/or composition of PrP Sc populations in response to replication in vitro (23). To what extent can strains be changed in PMCA?…”
mentioning
confidence: 99%
“…Recent studies concluded that the ratio of the infectivity titer to the amount of PrP TSE (specific infectivity) is much lower when the PrP TSE is generated by amplification in vitro than in infected brain-derived samples (15). Thus, while misfolded protein is readily generated in these assays, it is clear that not all the misfolded protein is infectious.…”
Section: Based On the Hypothesis That Prpmentioning
confidence: 99%